Peran IQ, EQ, SQ, Kecerdasan Sosial, dan Perilaku Belajar dalam Membentuk Pemahaman Akademik dan Perilaku Etis Mahasiswa: Kajian Literatur - Kausar Sihombing; Naufal Haadi; Rifqi Alhafizh; Sri Mulyeni (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Academic success and ethical behavior among students cannot be explained solely by cognitive ability. This article presents a literature review of scientific journal articles published between 2021 and 2025 that discuss the role of intellectual intelligence (IQ), emotional intelligence (EQ), spiritual intelligence (SQ), social intelligence, and learning behavior in shaping students' academic understanding and ethical behavior. The method used was a literature study by selecting, grouping, and synthesizing research findings based on topic relevance and source credibility. The synthesis results show that IQ plays a strong role in analytical and problem-solving aspects, EQ helps with emotion regulation, motivation, and adaptability, SQ strengthens value orientation and integrity, while social intelligence and learning behavior become important bridges through interaction, collaboration, and consistent learning habits. In addition, various studies show that the combination of these five aspects contributes significantly to improving conceptual understanding, decision-making skills, and the formation of ethical attitudes in an academic context. Students with a balance of IQ, EQ, and SQ tend to be better able to manage academic pressure, face failure as a learning process, and maintain consistency in achieving learning goals. Social intelligence strengthens the ability to collaborate, appreciate differences, and build effective communication, while positive learning behavior reflects discipline, responsibility, and commitment to the academic process. These findings emphasize the importance of a holistic approach to student development, not only emphasizing cognitive achievement but also nurturing emotions, values, and learning habits.